Analysis Of Determination On The Efficiency Of Multifinance Companies In Indonesia - Retno Ariani; Dwi Nastiti Danarsari (UIN Mataram, 2021)
A multifinance institution is a non-bank financial institution that lends money to customers or debtors in order to conduct a service or goods transaction. The multifinance industry has faced a number of issues in recent years, one of which is an increase in non-performing loans as a result of a decline in industrial growth, which has resulted in an increase in the ratio of NPLs, necessitating a re-evaluation. This study was carried out to assess the performance of multifinance companies in Indonesia from 2014 to 2019 and to identify the factors that influence it, so that the company can improve the relevant variables and increase company efficiency in the future. This study used the Stochastic Frontier Analysis (SFA) and Data Envelopment Analysis (DEA) methods to obtain the efficiency score and then using Tobit regression to determine which factors have an impact on efficiency. The results show that the Capital ratio, Size, Expense, ROA, and Borrowed Fund have a significant effect on multifinance efficiency in 2014-2019, with the capital ratio, ROA, and Borrowed Fund having a significant positive effect on efficiency, while Size and Expense have a significant negative effect on efficiency.